The Effect of STREAM-Based Teaching Materials Using Smart Apps Creator 3 on Students’ Scientific Literacy - Pebriani, Fenny; Heliawati, Leny; Ardianto, Didit (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
This study aimed to develop STREAM-based water teaching using Smart Apps Creator 3 on students’ scientific literacy. The method carried out by Research and Development uses the 4D design (Define, Design, Develop and Disseminate). The research data were collected and analyzed in the form of quantitative descriptive from the students’ pre-test and post-test results. This research used a Google form by distributing a questionnaire given to students with 56 respondents and 11 science teachers who had used STREAM-based water teaching materials using SAC 3. The results of the study, the average percentage of scientific literacy with N-Gain was 76% with a tall category, which means that the application of learning materials based on STREAM using Smart Apps Creator 3 is proven to improve student learning. Conclusion in this study is STREAM-based teaching materials using SAC 3 are statistically proven to improve students’ scientific literacy to water material in online learning during the current pandemic.